The Evolution of C4 Photosynthesis in Flaveria (Asteraceae): Insights from the Flaveria linearis Complex. Issue 1 (6th October 2022) - Adachi, Shunsuke; Stata, Matt; Martin, Duncan G; Cheng, Shifeng; Liu, Hongbing; Zhu, Xin-Guang; Sage, Rowan F
Abstract: Flaveria is a leading model for C4 plant evolution due to the presence of a dozen C3 -C4 intermediate species, many of which are associated with a phylogenetic complex centered around Flaveria linearis . To investigate C4 evolution in Flaveria, we updated the Flaveria phylogeny and evaluated gas exchange, starch δ 13 C, and activity of C4 cycle enzymes in 19 Flaveria species and 28 populations within the F. linearis complex. A principal component analysis identified six functional clusters: (1) C3, (2) sub-C2, (3) full C2, (4) enriched C2, (5) sub-C4, and (6) fully C4 species. The sub-C2 species lacked a functional C4 cycle, while a gradient was present in the C2 clusters from little to modest C4 cycle activity as indicated by δ 13 C and enzyme activities. Three Yucatan populations of F. linearis had photosynthetic CO2 compensation points equivalent to C4 plants but showed little evidence for an enhanced C4 cycle, indicating they have an optimized C2 pathway that recaptures all photorespired CO2 in the bundle sheath (BS) tissue. All C2 species had enhanced aspartate aminotransferase activity relative to C3 species and most had enhanced alanine aminotransferase activity. These aminotransferases form aspartate and alanine from glutamate and in doing so could help return photorespiratory nitrogen (N) from BS to mesophyll cells, preventing glutamate feedback onto photorespiratory N assimilation. Their use requires upregulation of parts of the C4 metabolic cycle to generate carbon skeletons to sustain N return to the mesophyll, and thus could facilitate the evolution of the full C4 photosynthetic pathway. Abstract : Forty-five genotypes of Flaveria species expressing the C3 and C4 photosynthetic pathways display physiological trait diversity and a wide range of C3 -C4 intermediate character states.